(untitled) (Colombia Medica, 2024)
Perifoliculitis capitis abscedens et suffodiens, dissecting folliculitis, dissecting cellulitis, or Hoffman disease is a rare, inflammatory and chronic condition, which affects the scalp of young black men, mainly characterized by the appearance of nodules and abscesses that drain purulent material with fistulas and pathways, leading ultimately to scarring alopecia. At present, this condition is defined as a primary disorder of follicular keratinization, being part of the triad or tetrad of follicular occlusion. One third of the cases are associated with acne conglobata as a primary event. Management, frustrating for many years, is promising with the successful use of isotretinoin and a combination of medications that intervene each of its physiopathological principles.